Urinary concentrations of 3-(diethylcarbamoyl)benzoic acid (DCBA), a major metabolite of N,N-diethyl-m-toluamide (DEET) and semen parameters among men attending a fertility center - Segal, Thalia R (Hum Reprod, 2017)
STUDY QUESTION: Are specific gravity (SG)-adjusted urinary concentrations of 3-(diethylcarbamoyl)benzoic acid (DCBA) associated with semen parameters among men attending an academic fertility center? SUMMARY ANSWER: Our study did not demonstrate any association between SG-adjusted urinary DCBA concentrations and semen parameters among men attending an academic fertility center. WHAT IS KNOWN ALREADY: N,N-Diethyl-m-toluamide (DEET) is the most common active ingredient in consumer insect repellents. The recent rise in public health concerns regarding mosquito-borne diseases such as Zika, have led to an increased use of DEET insect repellents, especially among couples planning pregnancy. Animal studies have observed reproductive toxicity from DEET exposure. However, the reproductive health effects of DEET and its metabolites on human reproduction are unknown. STUDY DESIGN, SIZE, DURATION: Between 2007 and 2015, 90 men participating in a prospective cohort study at the Massachusetts General Hospital Fertility Center provided 171 urine samples and 250 semen samples for analysis. PARTICIPANTS/MATERIALS, SETTING, METHODS: The urinary concentrations of DEET, N,N-diethyl-3-hydroxymethylbenzamide (DHMB) and DCBA were quantified by isotope-dilution tandem mass spectrometry and adjusted by SG. We used linear mixed models to evaluate the association between tertiles of SG-adjusted urinary DCBA concentrations and semen parameters (semen volume, sperm concentration, total sperm count, progressive motility, total progressive motility count, normal morphology and total normal morphology count), adjusting for covariates. DEET and DHMB were not considered for analysis because of the low percentage of detectable concentrations (<7%). Effect modification by BMI and smoking status was explored. MAIN RESULTS AND THE ROLE OF CHANCE: Participants had a median age of 36 years and BMI of 27 kg/m(2), and 68% had never smoked. The SG-adjusted geometric mean DCBA urinary concentration was 2.20 μg/l, with 85% detection frequency. The majority of semen parameters fell within the normal range with the exception of progressive motility, where 64% of the men had values below the WHO 2010 lower reference limits. SG-adjusted urinary DCBA concentrations were not associated with semen parameters in unadjusted or adjusted models. Men in the highest tertile of SG-adjusted urinary DCBA concentrations had comparable semen parameters to men in the lowest tertile (2.59 vs. 2.88 ml for semen volume, 47.9 vs. 45.8 million/ml for sperm concentration, 116 vs. 118 million for total sperm count, 25 vs. 24% for progressive sperm motility, and 6.1 vs. 5.8% for morphologically normal sperm). In addition, BMI and smoking status did not modify the associations. LIMITATIONS REASONS FOR CAUTION: We had a relatively small sample size with similar socioeconomic backgrounds and with overall relatively low urinary concentrations of DEET biomarkers. However, our sample size was enough to detect moderate differences with at least 80% statistical power, between the first and third tertiles of urinary DCBA concentrations. Limitations also include possible misclassification of DCBA exposure and difficulties in extrapolating the findings to the general population. WIDER IMPLICATIONS OF THE FINDINGS: Our study found no associations between urinary concentrations of DCBA, a major metabolite of the insect repellent DEET, and semen parameters in men presenting for infertility treatment. While these results are reassuring, further studies including larger sample sizes and higher exposures are warranted. STUDY FUNDING/COMPETING INTEREST(S): The project was financed by the National Institute of Health grants R01ES022955 and R01ES009718 and by grant P30ES000002 from the National Institute of Environmental Health Sciences (NIEHS). None of the authors has any conflicts of interest to declare. The findings and conclusions in this report are those of the authors and do not necessarily represent the official position of the Centers for Disease Control and Prevention. TRIAL REGISTRATION NUMBER: N/A.